Oil palm shell as a lightweight aggregate for production high strength lightweight concrete - Shafigh, P.; Jumaat, Mohd Zamin; Mahmud, H. (Elsevier, 2011)
In Malaysia, oil palm shell (OPS) is an agricultural solid waste originating from the palm oil industry. In this investigation old OPS was used for production of high strength lightweight concrete (HSLC). The density, air content, workability, cube compressive strength and water absorption were measured. The effect of five types of curing conditions on 28-day compressive strength was studied. The test results showed that by incorporating limestone powder and without it, it is possible to produce the OPS concretes with 28-day compressive strength of about 43-48 MPa and dry density of about 1870-1990 kg/m(3). The compressive strength of UPS HSLC is sensitive to the lack of curing. The water absorption of these concretes is in the range of good concretes.